DEM investigation on strain localization in a dense periodic granular assembly with high coordination number - Trung-Kien Nguyen; Thanh-Trung Vo; Nhu-Hoang Nguyen (Fracture and Structural Integrity)
Strain localization is one of key phenomena which have been studied extensively in geomaterials and for different kinds of materials including metals and polymers. This well-known phenomenon appears when structure/material is closed to failure. Theoretical, experimental, and numerical research have been dedicated to this subject for a long while. In the numerical aspects, strain localization inside the periodic granular assembly has not been well studied in the literature. In this paper, we investigate the occurrence and development of strain localization within a dense cohesive-frictional granular assembly with high coordination number under bi-periodic boundary conditions by Discrete Element Modeling (DEM). The granular assembly is composed of 2D circular disks and subjected to biaxial loading with constant lateral pressure. The results show that the formation of shear bands is of periodic type, consistent with the boundary conditions. This formation has the origins of the irreversible losing of cohesive contacts, viewed as micro-crackings which strongly concentrated in the periodic shear zones. This micromechanical feature is therefore strongly related to the strain localization observed at the sample scale. Finally, we also show that the strain localization is in perfect agreement with the sample’s displacement fluctuation fields.